Contextualized strategies to improve textual comprehension in natural sciences - Hernández Hernández, Candelaria (2023)
Textual comprehension is a fundamental learning process that facilitated the acquisition of new knowledge at the Río Grande de la Magdalena Educational Institution, where weaknesses were identified in sixth grade students through written diagnostic tests, consultation with members of the educational community, analysis of results of internal - external tests and surveys applied to all the actors involved in the educational process. The intervention proposed in the action research focused on improving the findings detected during the investigation. The didactic strategies that were implemented to strengthen reading comprehension are contextualized, taking advantage of the resources that the Momposina river region has. Workshops with on-site assisted guides were developed as a favorable and non-restrictive instrument to demonstrate the strategy, with community projection through echo murals and ICT elements such as the blog, which allowed the research to be globalized; also with qualitative tools to evaluate the intervention. It is noteworthy that there is evidence of improvements in the results of internal tests and a high institutional impact that led to the revision and updating of the curriculum in the area of Natural Sciences.